Testing a model of resilience for women leaders: a strengths based approach - Daphne Pillay-Naidoo; Petrus Nel (Australian Journal of Psychology, 2022)
Objective The aim of this study was to investigate the indirect processes through which cognitive, emotional and behavioural assets function to explain resilience amongst women leaders in higher education institutions. Method A quantitative cross-sectional survey design with a sample of N = 255 women leaders from higher education institutions was employed. Results All the proposed indirect pathways were found to be statistically significant and explained a fair proportion of the variance in the resilience scores of women leaders. Results revealed that cognitive assets (self-efficacy and mindfulness) were associated with resilience through association with emotional assets (positive affect and self-regulation) and behavioural assets (problem-solving skills and authentic functioning), both individually and in serial. Conclusions This study offers support for the direct and indirect relationships between mindfulness, self-efficacy, self-regulation, positive affect, authentic functioning, problem solving skills and resilience. It further generates new insights into the indirect processes through which cognitive, emotional and behavioural domains of influence may explain resilience amongst women leaders. KEY POINTS What is already known about this topic: Women leaders remain underrepresented in higher education institutions when compared to their male counterparts. Women leaders who possess higher levels of resilience are more likely to overcome the numerous barriers women face in higher education institutions when compared women leaders with lower levels of resilience. There is an established direct relationship between personal strengths such as self-efficacy, self-regulation and problem-solving ability and resilience. What this topic adds: By investigating the proposed indirect pathways and the interaction between cognitive, emotional and behavioural assets, this study offers a more nuanced approach to understanding the processes that lead to resilience. Using the cognitive-behavioural perspective of psychology as the theoretical framework to support the hypotheses proposed, this study expands the application of the cognitive behavioural model to explain resilience in the work context. This study offers support for a newly proposed model of cognitive, emotional and behavioural domains of influence on resilience.